Influence of sodium nitroprusside, nitric oxide donor, on growth and development of fruit in gobhi sarson (Brassica napus) - Jhanji, Shalini; Setia, R C; Setia, Neelam (The Indian Journal of Agricultural Sciences, 2012)
Foliar spraying of sodium nitroprusside (SNP), nitric oxide (NO) donor, on gobhi sarson [Brassica napus (cv. GSL 1)] plants, at green floral bud stage of terminal inflorescence ,exerted a profound effect on growth and metabolism of fruits(siliquae).SNP at all concentrations (50, 100, 200 and 400 µg/ml)caused significant increase in siliqua length and seed number/siliqua. In SNP-treated plants the siliquae were darker green, and during active phases of growth the siliqua wall and seed had higher total chlorophyll (chl) content, altered chl a/b ratios and greater Hill reaction activity of chloroplasts in comparison to control. This in turn resulted in increased accumulation of dry matter in siliquae of SNP-treated plants than controls. SNP enhanced the level of total soluble sugars, starch, total soluble proteins and free amino acids in both siliqua wall and seed during different developmental stages as compared to controls. The seed oil content increased by 2.27 percentage points with a treatment of 100 µg/ml SNP.